Yield performance and stability of modern breeding stock of spring durum wheat (Triticum durum Desf.) from Russia and Kazakhstan - P. N. Mal’chikov; M. A. Rozova; A. I. Morgunov; M. G. Myasnikova; Yu. I. Zelensky (Вавиловский журнал генетики и селекции)
Identifcation of adaptive responses of breeding material, developed in diﬀerent breeding centers, helps to purposefully correct these traits where it is necessary. Thus, 42 modern breeding lines from eight institutions of Russia and Kazakhstan were studied in comparison with the historical standard Bezenchukskaya 139 in trails of 16-17 and 18 KASIB-SDW (Kazakhstan-Siberian net for wheat improvement, spring durum wheat) in 2015–2017. Field experiments and yield measurements in each ecological cite were similar. To solve these tasks of the experiment, two-factor ANOVA, methods for adaptability assessment cluster analysis and principle component method were applied. As a result, it was established that 1) genotype and genotype – environment interaction (overall 15.8–23.5 % of total dispersion) had signifcant eﬀect on yield variability; 2) genotype – environment interactions were of linear nature and had no destabilizing eﬀect; 3) all the genotypes tested can be distributed in three clusters, the frst one for locally adapted varieties, the third for varieties of a wide areal, the second included genotypes with intermediate characteristics; 4) breeding centers of the Federal Altai Scientifc Centre of Agro-Biotechnologies and of the Research Institute of Agriculture of South-East produced predominantly varieties of local importance, the Samara Research Institute of Agriculture – varieties of wide area; 5) a stable trend of increased mean yield compared to historical standard Bezenchukskaya 139 over ecological sites was observed only for Samara varieties; 6) varieties of all the breeding centers had no stable diﬀerence from Bezenchukskaya 139 concerning stability and responsiveness, which can be explained by an incomplete breeding process for these parameters and confrms the importance of the KASIB program; 7) a trend of yield increase compared to Bezenchukskaya 139 under testing in defnite local environments had more stable parameters with the largest progress observed in the Altai Research Institute of Agriculture (135.4 and 163.2 % to Bezenchukskaya 139), which can be explained by a high efciency of breeding of locally adapted varieties in the breeding center.